Classifying Thermal Climate Zones to Support Urban Environmental Planning and Management in the Bangkok Metropolitan Area - Srivanit, Manat; Hokao, Kazunori; Iamtrakul, Pawinee (Journal of Architectural/Planning Research and Studies (JARS), 2014)
The Thermal Climate Zone (TCZ) is the basic unit of urban planning, defined as an area of thermally homogenous surface structure and cover, which was used in a GIS-multivariate analysis approach to delineate thermal climate units. With an understanding of the thermal impacts that planning decisions can have, it is essential to know how TCZs can be designed to regulate temperatures in the urban environment. Our aim in this study was twofold: 1) to facilitate consistent documentation of zone metadata and thereby improve the basis of intersite comparisons, and 2) to provide an objective protocol for measuring the magnitude of the urban heat island effect in the city. The analysis presented was applied on Bangkok Metropolitan Area. By surface properties differentiation, the urban-rural continuum yields a hierarchy of 7 TCZs. Land surface temperature was extracted from daytime LANDSAT TM (April 25th, 2009) image which was used to represent the stability of summer tem-peratures for different TCZs. We found that an urban–rural temperature difference, or urban heat island intensity, can often exceed 4.23°C in the summer. A spatially exhaustive map of TCZ would be helpful for city planners for two reasons. First, it would localize urban areas concerned by different climate behavior over the summer season and represented as a good indicator of urban climate variability. Second, when overlaid with a land cover map, this TCZ map may contribute to the identification of possible urban management strategies to reduce heat wave effects in the city. These results are clearly useful and essential pieces of information that can be applied in urban planning to improve climate adaptability.